Spastic Paraplegia Type 78 Associated With ATP13A2 Gene Variants in Compound Heterozygosity - R. Bermejo Ramírez; N. Villena Gascó; L. Ruiz Palmero; G. A. Ribes Bueno; E. Seiti Yamanaka; J. D. Arroyo Andújar (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Spastic Paraplegia Type 78 (SPG78) is a rare form of hereditary spastic paraplegia (HSP), mainly characterized by late‐onset lower‐limb spasticity, muscle weakness, and in some cases cerebellar dysfunction and cognitive impairment. Understanding its genetic background is essential to distinguish it from other autosomal recessive types of HSP. Methods A pathogenic variant screening in a Spanish HSP patient was carried out by whole‐exome sequencing, followed by a software filtering process and validation of candidate variants by Sanger sequencing. The pathogenicity of the selected variants was evaluated by In Silico predictions and a segregation analysis including the proband and 16 family members. Results Two variants in the ATP13A2 gene, predicted to have damaging effects by In Silico analyses, were considered potentially pathogenic: NM022089.4:c.649G>A (rs199961048), previously associated with SPG78 but with uncertain clinical significance, and NM_022089.4:c.2097delC, an unreported variant. The segregation analysis revealed that both variants were present in compound heterozygosity in the proband and two affected siblings, while unaffected relatives carried only one or none of the variants. Conclusion These findings suggest that the two variants are pathogenic when occurring in compound heterozygosity and, therefore, should be included in the genetic spectrum of SPG78 diagnosis.